Light Sensor Based Automatic Lamp Simulation Using Proteus - Ibnu Saputro (Journal of Educational Engineering and Environment, 2024)
Automatic lights with light sensors are lights that can turn on and off automatically without using a switch. The light sensor in automatic lights works by converting light quantities into electrical quantities. The working principle is that when the sensor detects the presence of light, the light will turn off, and vice versa. Here are some of the benefits of using automatic lights with light sensors: Save energy and reduce electricity bills, Increase comfort, Reduce the need to adjust lighting manually, Save labor and time. Light sensors work by utilizing the principles of electric current and resistance. When light hits the sensor, the resistance will increase or decrease according to its position, thereby regulating the current